A new quadrature sinusoidal oscillator for telecommunication system using VDDDAs - Chaichana, Amornchai; Jaikla, Winai; Suwanjan, Peerawut; Tuntrakool, Sunti (My University, 2016)
A CMOS voltage differencing differential difference amplifiers (VDDDAs) based voltage-mode quadrature sinusoidal oscillator is proposed. The proposed oscillator is based on the two integrator loop configuration with amplifier wherein the frequency of oscillation (FO) is tuned by the time constant of two integrator and the condition of oscillation (CO) is tuned by gain of amplifier. It is constructed from two VDDDAs, two resistors, and two grounded capacitors. With this structure, it is attractive to develop in monolithic chip. The tuning of frequency of oscillation can be electronically done without affecting the condition of oscillation. Also, the condition of oscillation can be adjusted by external resistor without affecting to frequency of oscillation. The simulation results have been demonstrated and discussed using parameters of 0.18um TSMC CMOS technology and +0.9V power supply voltages.
Keywords: CMOS; quadrature oscillator; sinusoidal signal; VDDDA; voltag-mode